Efficacy and Safety of Makabuhay (Tinospora rumphii) 25% Cream Versus Hydrocortisone 1% Cream in the Management of Mosquito Bite Reactions: Randomized Double-Blind Controlled Trial - Julius Garcia Gatmaitan; Jolene Kristine Garcia Gatmaitan-Dumlao; Johannes Dayrit; Ma Teresita Gabriel (JMIR Publications, 2023)
BackgroundMost insect bite reactions resolve spontaneously, but the inflammation and pruritus induced have been shown to decrease the quality of life. Previous studies have shown the potential anti-inflammatory properties of Tinospora rumphii. ObjectiveThe aim of the study is to assess the efficacy and safety of T rumphii 25% cream versus hydrocortisone 1% cream in the management of local cutaneous reactions caused by mosquito bites. MethodsThis study was a parallel-group, double-blind, randomized, placebo-controlled trial with a 1-week duration in a span of 3 months (June 2019 to August 2019). Participants were exposed to sterile noninfectious mosquitoes (Aedes aegypti) for 5-10 minutes to elicit cutaneous lesions. Tinospora 25% cream or hydrocortisone 1% cream was applied twice daily throughout the 7-day study period. Of the 70 participants screened for this study, which was approved by an institutional review board (IRB 2019-07) at the Dermatology Outpatient Department of the Research Institute for Tropical Medicine, Alabang, Muntinlupa, Philippines, 58 participants in total met the inclusion criteria and were randomized to treatment (Tinospora: n=29) and active control (hydrocortisone: n=29) groups. ResultsIn total, 58 participants were randomized to receive Tinospora cream (n=29) or hydrocortisone cream (n=29). All participants completed the follow-up. There was a significant decrease in lesion size in both groups from the first 15 minutes to day 7 (P<.001). Comparing the lesion size in both groups, there was a statistically significant decrease in lesion size in the first hour (P=.003) and after 24 hours (P=.03). On day 1, 10% (n=29) of participants in the hydrocortisone group and 7% (n=29) in the Tinospora group experienced complete resolution. On day 3, all participants experienced complete resolution. No adverse effects were documented. ConclusionsTinospora 25% cream is safe, effective, and comparable to hydrocortisone 1% cream as an anti-inflammatory agent for mosquito bite reactions based on the decrease in lesion size, the proportion of participants with complete resolution of wheals, and improvement in pruritus intensity score using a visual analog scale. Long-term safety studies are recommended. Trial RegistrationPhilippine Health Research Registry PHRR230716-005932; https://www.herdin.ph/index.php/registry?view=research&layout=details&cid=5932